2020
DOI: 10.1016/j.eclinm.2020.100296
|View full text |Cite
|
Sign up to set email alerts
|

Violence-related knife injuries in a UK city; epidemiology and impact on secondary care resources

Abstract: Background: The incidence of knife-related injuries is rising across the UK. This study aimed to determine the spectrum of knife-related injuries in a major UK city, with regards to patient and injury characteristics. A secondary aim was to quantify their impact on secondary care resources. Methods: Observational study of patients aged 16+ years admitted to a major trauma centre following kniferelated injuries resulting from interpersonal violence (May 2015 to April 2018). Patients were identified using Emerge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
28
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 14 publications
3
28
1
Order By: Relevance
“…Other studies concur that young males are most likely to sustain these injuries [ 1 , 5 7 , 9 , 21 ], most often from knives [ 1 , 6 , 9 ]. Peak occurrence from late evening to early morning is noted elsewhere (particularly Friday, Saturday and Sunday) [ 1 ], with earlier peaks for younger patients [ 21 ]. Annual patterns vary, with peaks noted in summer [ 1 ] and winter [ 9 ].…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…Other studies concur that young males are most likely to sustain these injuries [ 1 , 5 7 , 9 , 21 ], most often from knives [ 1 , 6 , 9 ]. Peak occurrence from late evening to early morning is noted elsewhere (particularly Friday, Saturday and Sunday) [ 1 ], with earlier peaks for younger patients [ 21 ]. Annual patterns vary, with peaks noted in summer [ 1 ] and winter [ 9 ].…”
Section: Discussionmentioning
confidence: 87%
“…Peak occurrence from late evening to early morning is noted elsewhere (particularly Friday, Saturday and Sunday) [ 1 ], with earlier peaks for younger patients [ 21 ]. Annual patterns vary, with peaks noted in summer [ 1 ] and winter [ 9 ]. There may be variations in factors between regions and different years.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Over a lifetime, more than 1 of 3 women (35.6%) and more than 1 of 4 men (28.5%) will have experienced physical violence, rape, and/or stalking by an intimate partner (Birkley & Eckhardt 2015;Tharp et al, 2013). Malik et al (2020) studied knife-related injuries and observed that female knife-injured patients were more likely to be injured in domestic violence circumstances (64.9% cases), and 16.2% of them were pregnant at the time of injury (Malik et al, 2020). Recent research has shown that repeated incidents of IPV had been registered by the police and/or by the health-and social care services before an intimate partner homicide case occurred.…”
Section: Discussionmentioning
confidence: 99%